Prophylactic OF THROMBOPHILIC COMPLICATIONS IN PREGNANT women WITH METABOLIC SYNDROM - O. Dyndar; V. Benyuk; V. Kurochka; A. Semenyuk (Bukovynian State Medical University, 2013)
The role of thrombophilia in pathogenesis of main obstetrics aftereffects of illness in women with metabolic syndrome has been studied out. The flow of pregnancy, childbirth and puerperal period in women with metabolic syndrome and genetic determinate hypofibrinolysis and multigens form of thrombophilia were analysed. The main concepts of the pregnancy preparations has been worked out. Pathologically grounded prophylactics with using low-molecular geparin, vitamins and antioxidants for women with metabolic syndrome was worked out.